Eco and user–friendly curcumin based nanocomposite forensic powder from coal fly ash for latent fingerprint detection in crime scenes - E. PRABAKARAN; K. PILLAY (Carbon Trends)
In this study, the production of an eco-friendly curcumin based nanocomposite fingerprint labeling powder is reported for the first time. This powder was prepared from thermal power plant waste known as coal fly ash. 3-aminopropyltrimethoxysilane (APTMS) was covalently interacted with coal fly ash (CFA/APTMS) and curcumin (CUR) was encapsulated onto CFA/APTMS to give a novel and eco-friendly CFA/APTMS/CUR nanocomposite for LFPs detection with the powder dusting method. Several instrumental techniques including Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), UV–visible spectroscopy, fluorescence spectroscopy (FL), scanning electron microscopy (SEM), energy-dispersive X-ray spectrometry (EDS), and transmission electron microscopy (TEM) were used to characterize this nanocomposite. The CFA/APTMS/CUR nanocomposite was applied as a forensic powder for the development of latent fingerprint (LFPs) images on various porous and non-porous substrates. Level 2 (island, origination, bifurcation, termination, fork, dot, and bridge) and Level 3 (sweat pores and shape of triangles, round, and irregular) were the features of the LFP images. Under visible light conditions, the aging LFPs images were clearly detected on an aluminum foil surface using the nanocomposite powder, which had good sensitivity and minimal background interference. Additionally, LFPs images were developed using CFA/APTMS/CUR nanocomposite on leather substrates for belts and shoes in order to confirm the benefits of the nanocomposite's high sensitivity. This nanocomposite improved LFPs images with unique patterns and showed excellent performance on a variety of surfaces for the development of LFPs. These findings therefore proved that the powdered CFA/APTMS/CUR nanocomposite can be effectively utilized for the development of LFPs images at important crime scenes and for the biometric identification of criminal suspects through fingerprint comparison.